Architecture shaped by socio-cultural influence and climate: Lessons learnt from study of vernacular architecture of Kerala - Dr. Janmejoy Gupta (1), Naushaba Jameel (2) & PushpitaPadhy (3). (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2020)
The vernacular architecture of any place is evolved through ages by consistent and continuous effort for more efficient solutions. Housing typologies though a result of multiple determinants, climate and culture are the two most important determinants. Materials, construction, and technology are best treated as modifying factors, rather than form determinants. This paper studies the evolution of vernacular architecture of Kerala in response to climatic conditions and varied cultural influences it has been subjected to. The orientation of buildings’, internal arrangement of spaces, the presence of internal court-yards, use of locally available materials and other socio-cultural factors have combined together to create the vernacular architecture as it exists today. Other than improved thermal comfort, the vernacular architecture of Kerala also gives a number of pointers towards betterment of architectural quality in modern architecture with respect to planning principles, aesthetics and building materials used in built form. Alongside, this paper also looks at the different architectural lessons that can be learnt from the vernacular architecture of Kerala to be applied to modern architecture practiced in Kerala to make it more culturally and climatologically contextual to Kerala.